The Impact of Enterprise Risk Management (ERM) on Firm Value in KBMI Category 4 Banks Listed on the Indonesia Stock Exchange - Mochammad Nugraha Reza Pradana; Amanda Novita Sari; Jane Lovita Putri; Nanvy Jenix Dean Polii; Jeslin Jeslin; Shela Agustina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study analyzes the impact of Enterprise Risk Management (ERM) disclosure on the value of firms within KBMI Category 4 banks listed on the Indonesia Stock Exchange from 2017 to 2024. The study used a quantitative associative methodology, using secondary data sourced from the annual reports and financial statements of four banks: PT Bank Central Asia Tbk., PT Bank Rakyat Indonesia (Persero) Tbk., PT Bank Mandiri (Persero) Tbk., and PT Bank Negara Indonesia (Persero) Tbk. Data were analyzed through multiple linear regression following classical assumption tests, which included assessments of normality, multicollinearity, and heteroscedasticity. The value of the firm was assessed utilizing Tobin's Q ratio. The findings indicate that ERM transparency and profitability, as measured by Return on Assets (ROA), do not have a substantial impact on business value. Conversely, leverage exerts a substantial adverse impact on business value. ERM, ROA, and leverage collectively account for 41.2% of the fluctuation in firm value, with the remaining 58.8% attributable to external factors not included in the model. The findings indicate that ERM disclosure has not emerged as a principal factor influencing firm value in KBMI 4 banks, highlighting the necessity to bolster risk management methods and promote transparency to elevate stakeholder confidence.